2006
DOI: 10.5424/sjar/2006041-173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of markets for irrigation water in the internal river basins of Catalonia, Spain

Abstract: Irrigated agriculture has come under close scrutiny in Europe recently because of its high share of total water consumption and its apparent inefficiency. Several water policies have been advocated, in particular the use of economic instruments such as water markets. This paper simulates the impact of a policy based upon water markets on agricultural production in the internal river basins of Catalonia (Spain). This zone presents certain particularities that make it very interesting to study: competition betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…These figures are low compared to other research, which report loss reductions up to 30% and 33% [50,77] in California and Spain. But these are close to other results, in Pujol et al (2016) [24], who report a total lose reduction up to 2.9%. They concluded that, although the water market has low economic gain compared with the scenario without water market, this policy might guarantee an optimal reassignment of the resource as well as a positive social impact and the water management by the water administration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These figures are low compared to other research, which report loss reductions up to 30% and 33% [50,77] in California and Spain. But these are close to other results, in Pujol et al (2016) [24], who report a total lose reduction up to 2.9%. They concluded that, although the water market has low economic gain compared with the scenario without water market, this policy might guarantee an optimal reassignment of the resource as well as a positive social impact and the water management by the water administration.…”
Section: Discussionsupporting
confidence: 91%
“…Other application for an irrigation water market evaluation and derived demand curves estimation were applied by Pujol et al [24], using a multicriteria decision model. Calatrava and Garrido [25] modeled a water market to reduce the exposure of farmers to risk associated with uncertain supply.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of the study area, which was affected by exceptional supply situations in 1999, 2000, 2002, 2005 and 2007-2009. Moreover, and assuming that farmers cannot choose a water source, and that they are forced to use reclaimed water, the current price would have different implications depending on the type of production. The demand curves determined by Pujol (2002) and Pujol et al (2006), for the irrigation of the Lower Ter River basin (where the experimental plot is located) show that the fruit orchards and ornamental plant nurseries in the area could pay the current price of reclaimed water but profits would be reduced, while farms producing fodder to feed their livestock would be in an extreme situation, and producers of corn and other cereals could not afford that price.…”
Section: Discussionmentioning
confidence: 99%
“…The request of the irrigators and broad social sectors at the Water Administration has resulted in a greater flow rate of the Ter River, reducing the water transfer to Barcelona metropolitan area. The implantation of markets for irrigation water in this irrigation area would guarantee the optimal reassignment of the resource during low-water periods to prevent conflicts; however, the irrigators would not accept this new tool and its associated transaction costs [53].…”
Section: The Baix Ter Irrigation Districtmentioning
confidence: 99%